Being before: three Deleuzian becomings in teacher education. Issue 2 (27th May 2021) - Adams, Erin
ABSTRACT: In this article, I use data from interviews with three social studies teachers to consider teachers' identity development. I point to how their narratives challenge traditional linear notions of professional attainment and apprenticeship by drawing on theories from Deleuze and Guattari as well as scholars in education who have utilised Deleuzian conceptions to theorise teacher education. Becoming teacher is a way for teachers and teacher educators to rethink professional identity for the fostering of justice and equity.